O papel da confiança nas alianças estratégicas em sistemas agroindustriais: o caso do tomate cereja no estado de Goiás, Brasil - Ferreira, Regiane Colatini Gomes (2019)
The Agroindustrial System (AS) is complex, dynamic and competitive. In this context, the agents acting in an AS need to choose strategies to deal with this environment. In this sense, firms should establish strategic alliances in order to get a competitive advantage. Strategic alliances are related to trade-based relationships and trust among agents. Thus, this study aims to assess the role of trust in establishment and sustainability of such strategic alliances in the type grape tomato agricultural system in Goiás State, Brasil. We rely on Strategic Alliance, Transaction Costs Economics and Trust literature as a theoretical framework. We use qualitative and descriptive techniques as a methodological framework. This methodology comprises semi-structured interviews and non- participative observations. The data will be interpreted by means of content analysis. Our analysis points out the main sources that enables trust in the relationship between grape-tomato growers and their partners: (1) Transference process, (2) Reputation, (3) Frequency e (4) ex-ante reputation. In addition, we shed a light on how trust directs strategic alliances by grape-tomato growers during the set up phase and strategic alliance maintenance. Therefore, this research presents an empirical contribution to the understanding on how trust affects interorganizational within the grape-tomato AS. Future research should increase the number of cases and rely on quantitative methods. The main take away relates to studies that capture the economic feasibility of strategic alliances in order to make a stronger point regarding financial aspects to agents intending to participate in a strategic alliance.